Rethinking the Implications of Large Eustachian Valve during Interventional and Surgical Atrial Septal Defect and Patent Foramen Ovale Closure Procedures - Onorato, Eustaquio Maria (Medical Research and Its Applications Vol. 8, 2024)
It is likely that a proportion of patients evaluated for transcatheter Patent Foramen Ovale (PFO) and ostium secundum Atrial Septal Defect (OS ASD) closure has actually different anatomical variants particularly common in the right atrium such as Eustachian valve (EV), Chiari network (CN), Thebesian valve and Crista Terminalis (CT). Notably, EV is usually considered to be a benign finding in the absence of associated cardiac anomalies, but it is frequently found in adult patients with septal abnormalities mainly PFO. Percutaneous PFO/OS ASD closure can be achieved safely and efficiently and nowadays represents a routine interventional procedure in the catheterization laboratory with two different clinical indications. PFO closure is usually effective in preventing recurrent embolic stroke/systemic arterial embolization having reduced the risk of recurrent stroke in patients with cryptogenic strokes in randomized clinical trials [1,2]. Of note, EV may actively facilitate the mechanism of paradoxical embolism by directing the blood from the Inferior Vena Cava (IVC) towards the interatrial septum via PFO into the left atrium. Therefore, the presence of such an anatomic variant may represent per se an increased risk factor for left circulation thromboembolism. OS ASD represents the second most common congenital heart defect, accounting for about 10% of all congenital heart defects in the adult population. ASD closure is indicated in patients with significant left-to-right shunt, right ventricular volume overload, and normal pulmonary vascular resistance. Transcatheter OS ASD closure using currently available devices has proven to be safe and effective in the majority of cases offering excellent closure rates and shorter hospital stays compared to surgery [3,4]. It is of paramount importance to identify by echocardiography imaging the EV and other anatomical variants in order to avoid misdiagnosis and complications when planning PFO/OS ASD percutaneous or surgical closure procedures where EV may interfere with a successful outcome.